Geeky f@b 5. #2, Mystery of the missing Monarchs - Lareau, Lucy; Lareau, Liz (Papercutz, 2019)
"The Geeky Fab Five discover a hidden garden filled with Monarch butterflies and honeybees. While the girls are learning in science class that Monarchs and bees are becoming endangered, something threatens their secret butterfly garden behind Earhart. To solve the mystery, Hubble the GFF mascot (and ever-so-curious cat) discovers a secret that gets him catnapped! In a race against time, the girls must rescue Hubble, save the garden, and solve the mystery of the missing Monarchs" --